Delayed Referral of a Neonate with Biliary Atresia Presenting as Jaundice: A Case Report - Zubaity Ardhanariswari; Rendi Aji Prihaningtyas; Muji Retnaning Rini; Muhammad Faizi; Bagus Setyoboedi (PT Dexa Medica, 2026)
Delayed diagnosis of cholestasis in infant remains a significant health problem. Cholestatic jaundice is a pathological condition that requires immediate treatment, particularly in cases such as biliary atresia. Biliary atresia is a progressivefibroinflammatory process that causes fibrosis in biliary tract, resulting in liver cirrhosis if left untreated. This case report aims to describe the delayed referral of biliary atresia in an infant. Case: A 3-month-old girl presented to a tertiary hospitalwith a chief complaint of jaundice. Jaundice had been present since the second day of life and persisted despite sun exposure and breastfeeding. The mother also reported abdominal distension, yellow-brown urine resembling tea, and palestools. Physical examination revealed hepatosplenomegaly. Laboratory results showed elevated liver enzymes (aspartate aminotransferase [AST] 237.4 U/l, alanine transaminase [ALT] 139 U/l, gamma-glutamyl transferase [GGT] 864 U/l), and cholestasis (total bilirubin 13.90 mg/dl, direct bilirubin 9.80 mg/dl). A two-phase abdominal ultrasound showed a gallbladder with preprandial size approximately 0.87 x 0.93 x 1.76 cm (length x width x height), with no contractility. Liver histopathologyrevealed extrahepatic cholestasis with extensive fibrosis (F3). The patient was diagnosed with biliary atresia and liver fibrosis and was subsequently referred for liver transplantation. Delayed referral of biliary atresia case is associated withpoor prognosis. Increasing awareness and health education among primary health providers, community health workers, and parents are essential for early detection of cholestasis, which can reduce morbidity, mortality, as well as the need for liver transplantation.